Essays on John Maynard Keynes - Keynes, Milo. (London : New York : Cambridge University Press, 1975)
This volume tries to provide a picture of the life of Maynard Keynes and his wide-ranging interests. it is in fact a biography by many authors; each contribution is written by an expert in the field it covers.
Includes bibliographical references and index.
ijb, 14/01/2019
Loans
Keywords: Keynes, John Maynard; Keynesian economics